Building handball game models - Mendes, José Carlos (2021)
Building handball models is very complex due to the multiple actions performed in attack and defense and the different individual, group, and collective tactical behaviors that must be appropriately structured to solve momentary game situations. Consequently, since coaches are the ones responsible for this process, this theoretical essay aims to address the role of coaches in building game models and to establish contents for the training process capable of promoting the player’s autonomy and creativity when making decisions. The current dynamics of elite handball requires coaches to have a high level of professional, interpersonal, and intrapersonal knowledge, in order to justifiably structure training tasks and problematic situations to be very similar to the actual game and allow for a more autonomous training of players. In this context, on the one hand, training tasks for the defensive phase must be developed with high demands for behaviors that would anticipate the attacker’s actions in greater depth. On the other hand, training tasks for the offensive phase must give players a diversified and varied role of tactical actions individual/group/collective technique in situations of extreme pressure with high levels of efficiency and effectiveness. Coaches must select, organize, and coordinate these actions as a unit for rational and timely use, mediated by the guiding principles of the players and the team, while giving teams an identity in the game.